Positive Polarity in Turkish: a Corpus-based Study of ‘Oldukça’ - Emrah Gorgülü (Akademik Dil ve Edebiyat Dergisi, 2026)
This paper is concerned with the syntactic and semantic properties of the degree adverb ‘oldukça’ in Turkish. In previous descriptive work, this adverb has been assigned various interpretations such as ‘quite’, ‘rather’ and ‘fairly’, generally appearing in the modifier position of another element. However, what is actually interesting about this lexical item is that its syntactic and semantic behavior seems to have significant implications for polarity sensitivity. Based on the findings of a corpus study (TS Corpus v2), I show that its syntactic distribution is rather constrained since it only appears in positive sentences, excluding negative ones as well as those like if-clauses and questions. Following recent work on polarity sensitivity in the language, I argue that the characteristics of oldukça can be accounted for by way of the semantic notion of (non)veridicality. In other words, oldukça occurs only in veridical contexts but not in nonveridical and antiveridical ones, which makes it a true positive polarity item. One implication of this study is that positive polarity items, just like their negative counterparts, come in different types and display certain variations both within and across languages.